SIFAT PEMESINAN BEBERAPA JENIS KAYU ASAL IRIAN JAYA - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Nine wood species collected from Sarong, Iriarn Jayo, were observed for their machining properties. Sawing characteristics (feed speed and surface smoothness) of each species were observed to determine its cutting-ability. Other machining properties (planing, shaping, boring. turning and sanding) were determined according to the modifled ASTM D-1666 method as festly described in the Forest Products Research Institute Report No. 160 (1982). Planing and shaping of samples were observed in wet condition (above EMC) and again after air-drying, whereas the remaining properties were observed only at air-dry condition.Results showed that most of the species couid be sawn fairly easily, and indicaud a variation in cutting surface qualjty, ranging from rough to smooth. One species, i.e., goh (T.richadenia phiilippinensis) was quite difficult to saw for its irregular (partly nterlocked) grain orientation and very high density. Testing of wood samples in wet condition produced a satisfactory planing and shaping quality for most wood species. However, testing at air-dry condition significantly revealed a better machining quality. Based on the machining characteristics observed on the nine wood species from Sorong, it is recommendable to use the timbers for woodworking purposes.